CATEGORICAL DEVICE OF MARKETING SUPPORT OF INNOVATIVE DEVELOPMENT OF TRANSPORT ENTERPRISES - Пілецька, С. Т.; Петровська, С. В.; Петровський, О. О. (Science-based technologies, 2019)
In solving the scientific task of developing theoretical and methodological principles and practical recommendations for the formation and implementation of marketing support for innovative development of transport enterprises, it is important to determine the essence and content of the concepts of "marketing support", "marketing support of innovation development", which has important scientific and practical value, since it will help to form recommendations on the organization of marketing provision of innovative development in the work of enterprises. The purpose of the research is to develop a categorical apparatus for providing marketing support to innovative development of enterprises. It is noted that in the theory and practice of marketing, the term "marketing support" is used by researchers and specialists in various contexts in the description of marketing activity, but, however, does not have a definite, agreed, clearly perceived meaning. This term is given partial, subjective, appealing to the intuitive perception, an additional meaning. It is substantiated that under the marketing support of innovation development it is necessary to understand the complex process of application of marketing principles and tools in order to create optimal conditions at enterprises for the search, selection, development and dissemination of technological, organizational, managerial and other decisions. Based on the principles of marketing and the essence of innovation development, the principles of marketing support for innovative development of the enterprise are defined: the principle of certainty of needs; principle of purposefulness; the principle of adaptation; the principle of interconnection. It is substantiated that marketing support of innovative development allows more efficient use of innovations and determines the necessity of developing an appropriate mechanism. The role of which is to provide guidance for further development in the market, it is a source of information for the innovative development of enterprises. To build an effective mechanism, it is necessary to use the information obtained on the basis of marketing market research, the state and degree of satisfaction of consumer demand for innovation, the main competitors and the scientific and technical level of domestic and foreign products. The value of marketing support in the implementation of innovative enterprise development enables to evaluate its possibilities depending on internal and external conditions and trends of their changes, which allows to increase the flexibility and adaptability of innovation activity to the environment and ensure the implementation of innovations